2019
DOI: 10.1371/journal.pone.0210854
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis EF-2001 protects DNBS-induced inflammatory bowel disease in mice model

Abstract: Recent studies have demonstrated the immunomodulatory effects of heat-killed lactic acid bacteria. The aim of this study was to evaluate the protective effect of heat-killed Enterococcus faecalis EF-2001 (EF-2001) on a model of inflammatory bowel disease (IBD). A total of 28 female NC/Nga mice were divided into 4 treatment groups. Controls were fed a normal commercial diet. In the experimental groups, colitis was induced by rectal administration of dinitrobenzene sulfonic acid. Two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
1
18
1
1
Order By: Relevance
“…This effect was similar to that of steroids, which are commonly prescribed for treating IBD [52]. Recently, other researchers have reported that EF-2001 protects dinitrobenzene sulfonic acid-induced colitis, a chemically induced colitis model, via a decrease in inflammatory cytokines [30]. Thus, the anti-inflammatory effect of EF-2001 may also be related to reduced inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This effect was similar to that of steroids, which are commonly prescribed for treating IBD [52]. Recently, other researchers have reported that EF-2001 protects dinitrobenzene sulfonic acid-induced colitis, a chemically induced colitis model, via a decrease in inflammatory cytokines [30]. Thus, the anti-inflammatory effect of EF-2001 may also be related to reduced inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 56%
“…NFκB p65 activation inhibits apoptosis by increasing X-linked inhibitor of apoptosis protein (XIAP), an anti-apoptotic factor that exerts its action by regulating caspase-3 activity [26, 27]. EF-2001 can decrease serum inflammatory cytokines in a contact dermatitis model mouse [28], has anti-tumor effects [29], and protects chemical-induced colitis [30]. Therefore, we hypothesized that EF-2001 may attenuate inflammation and apoptosis in DSS-treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…During this phase, the appearance of a series of IBS-like symptoms is observed: visceral hypersensitivity, motility disorder and alterations of the permeability or the secretion that also persist in the animals during the phase of recovery from the colitis [30]. Moreover, DNBS also causes IBD-like symptoms such as intestinal mucosal and transmural damage, intestinal motility dysfunction, release of pro-inflammatory cytokines, and dysbiosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…LAB have shown that can counteract inflammatory processes in the GIT through different mechanisms, this was demonstrated using animal models of IBD and intestinal mucositis (IM), and in clinical trials, being the intestinal microbiota and host's immune response modulation the most evaluated (dos Ferreira dos Santos et al 2016;Tang et al 2017;Yokota et al 2018;Choi et al 2019).…”
Section: Vitamin Production By Lab To Counteract Intestinal Inflammationmentioning
confidence: 99%